Technological Model Based on Blockchain Technology for Genetic Information Protection in the Health Sector - Arroyo-Mariños, Julio (2023)
In the health industry, the transparency of product data registration in the supply chain is a critical aspect in determining the source of genetic data. Various upcoming technologies, such as blockchain, can help with this challenge. Blockchain is a shared and immutable database that makes recording transactions and tracking assets in a commercial network easier. Currently, genetic information is regarded as a vital asset in the health sector, as more precise diagnostic samples in medical genomics enable improved treatments for patients suffering from a variety of disorders. Since actions connected to the storage or management of data might have several areas of vulnerability, this paper describes the development of a technological model employing Blockchain as technology to assure the protection of genetic information in the private health sector. Furthermore, unauthorized activities such as registration and access control in the exchange of genetic information have been carried out, primarily through entities that manage the eligibility of users with genomics information and grant access to specific data sets, demonstrating a lack of harmonization in access policies between the owners of genetic information and the health entities that manage it. A proof-of-concept was carried out to evaluate the model’s capabilities and ensure that a larger-scale deployment could be carried out. Experts agreed with our proposal, and consumers would be prepared to employ proof of concept to assure traceability and security of their data, according to the evaluation.